(untitled) (Journal of Human Sciences, 2026)
This study addressed issues related to the preferred opinions of Sheikh Ahmad bin Muhammad Al-Tawil in his book Wahat Al-Tafsir. The aim of this study was to highlight the preferences adopted by the author among the opinions of scholars, to examine them through a comparative study, and to identify the aspects and expressions of preference he employed. The researcher adopted an inductive, analytical, and comparative methodology in this study. The findings revealed that the author, in many of his preferences, agreed with the views held by the majority of scholars, including jurists and exegetes, while employing a variety of approaches and expressions in making his preferences. Due to the nature of the research, it was divided into an introduction and a preface, followed by three main topics: The first: issues related to the author’s preferences in the chapters of Al-Isra and Al-Kahf; The second: issues related to the author’s preferences in the chapters of Maryam and Al-Anbiya; The third: issues related to the author’s preferences in the chapters of Al-Nur, Al-Ankabut, and Al-Ahzab. The study concluded with a summary containing the most important findings and recommendations reached by the researcher.